The numerical analysis of non-newtonian blood flow in a mechanical heart valve - Chen, Aolin; Basri, Adi Azriff; Ismail, Norzian; Ahmad, Kamarul Arifin (Multidisciplinary Digital Publishing Institute, 2022)
Background: The non-physiological structure of mechanical heart valves (MHVs) affects the blood flow field, especially the complex microstructure at the hinge. Numerous studies suggest that the blood flow field in the aortic area with an MHV can be considered Newtonian. However, the Newtonian assumption is occasionally unreasonable, where blood viscosity changes with shear rate, exhibiting non-Newtonian shear-thinning characteristics. Methods: In this research, a comprehensive study of the non-Newtonian effects on the hemodynamic behavior of MHVs was performed. The impact of the Newtonian hypothesis was investigated on the internal hemodynamics of MHVs. Several non-Newtonian and Newtonian models were used to analyze the chamber flow and blood viscosity. MHVs were modeled and placed in simplified arteries. After the unstructured mesh was generated, a simulation was performed in OpenFOAM to analyze its hemodynamic parameters. Results: In the study of the non-Newtonian viscosity model, the Casson model differs significantly from the Newtonian model, resulting in a 70.34% higher wall shear stress. In the modified Cross and Carreau models, the non-Newtonian behavior can significantly simulate blood in the MHV at different stages during initial and intermediate deceleration. The narrowing of the hinge region in particular, has a significant impact on evaluating blood rheology. The low flow rate and high wall shear force at the hinge can cause blood cell accumulation and injury time, resulting in hemolytic thrombosis. Conclusion: The results exhibit that the Newtonian hypothesis underestimates the hemodynamics of MHVs, whose complex structure leads to increased recirculation, stagnation, and eddy current structure, and a reasonable choice of blood viscosity model may improve the result accuracy. Modfied Cross and Carreau viscosity models effectively exhibit the shear-thinning behavior in MHV blood simulations.